In Vitro N -Glycan Mannosyl-Phosphorylation of a Therapeutic Enzyme by Using Recombinant Mnn14 Produced from Pichia pastoris - Kang, Ji-Yeon; Choi, Hong-Yeol; Kim, Dong-Il; Kwon, Ohsuk; Oh, Doo-Byoung (Journal of microbiology and biotechnology, 2021)
Enzyme replacement therapy for lysosomal storage diseases usually requires recombinant enzymes containing mannose-6-phosphate (M6P) glycans for cellular uptake and lysosomal targeting. For the first time, a strategy is established here for the in vitro mannosyl-phosphorylation of high-mannose type -glycans that utilizes a recombinant Mnn14 protein derived from . Among a series of N-terminal- or C-terminal-deleted recombinant Mnn14 proteins expressed in , rMnn14 with deletion of N-terminal 76 amino acids spanning the transmembrane domain (46 amino acids) and part of the stem region (30 amino acids), showed the highest level of mannosyl-phosphorylation activity. The optimum reaction conditions for rMnn14 were determined through enzyme assays with a high-mannose type -glycan (Man GlcNAc ) as a substrate. In addition, rMnn14 was shown to mannosyl-phosphorylate high-mannose type Nglycans (Man GlcNAc ) on recombinant human lysosomal alpha-glucosidase (rhGAA) with remarkably high efficiency. Moreover, the majority of the resulting mannosyl-phosphorylated glycans were bis-form which can be converted to bis-phosphorylated M6P glycans having a superior lysosomal targeting capability. An in vitro -glycan mannosyl-phosphorylation reaction using rMnn14 will provide a flexible and straightforward method to increase the M6P glycan content for the generation of "Biobetter" therapeutic enzymes.